2019
DOI: 10.1186/s12872-019-1072-9
|View full text |Cite
|
Sign up to set email alerts
|

Female sex and cardiovascular disease risk in rural Uganda: a cross-sectional, population-based study

Abstract: Background Sex-based differences in cardiovascular disease (CVD) burden are widely acknowledged, with male sex considered a risk factor in high-income settings. However, these relationships have not been examined in sub-Saharan Africa (SSA). We aimed to apply the American Heart Association (AHA) ideal cardiovascular health (CVH) tool modified by the addition of C-reactive protein (CRP) to examine potential sex-based differences in the prevalence of CVD risk in rural Uganda. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
20
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 41 publications
6
20
2
Order By: Relevance
“…We found that baseline HbA1c was associated with future risk of CAP in women, but not in men. Consistent with our results, one previous study found that chronic hyperglycemia was associated with a higher risk of cardiovascular diseases in women, but not in men [36]. The results of meta-analysis also demonstrated that sex might modulate the risk of type 2 diabetes [37] and stroke [38] in adult patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that baseline HbA1c was associated with future risk of CAP in women, but not in men. Consistent with our results, one previous study found that chronic hyperglycemia was associated with a higher risk of cardiovascular diseases in women, but not in men [36]. The results of meta-analysis also demonstrated that sex might modulate the risk of type 2 diabetes [37] and stroke [38] in adult patients.…”
Section: Discussionsupporting
confidence: 92%
“…The underlying mechanism remained unclear. However, sex is considered as a biological variable underlies physiological variation in vascular function, fibrinogen, and coagulation [36, 41]. Sex hormones could contribute to the progress of macrovascular related diseases [42].…”
Section: Discussionmentioning
confidence: 99%
“…As discussed above, cross-sectional studies have demonstrated increased prevalence of a variety of CVD risk factors (obesity, dyslipidemia and HTN) among women in SSA compared to men, with significant variation depending on the population that is studied. 85,86 One potential contributor to sex-determined CVD risk is pregnancy-related physiologic changes and its' downstream effects on chronic health. Hypertensive disorders of pregnancy (HDP), are a major cause of mortality and morbidity worldwide, complicating 5%-10% of all pregnancies.…”
Section: Sexmentioning
confidence: 99%
“…Rural areas had lower riskfactors burden but higher age-standardized prevalence of CVDs compared with urban areas 40,41 , which might be due to the lower educational level, lower quality of health services, and less frequency of proven therapies used. Previous studies have reported that the prevalence of ICH was higher in women 26,27,42,43 . Similar results were found in our study.The age-standardized prevalence of ICHin men and women were 0.08% vs. 0.12%.…”
Section: Discussionmentioning
confidence: 85%